2020
DOI: 10.1016/j.jhepr.2020.100143
|View full text |Cite
|
Sign up to set email alerts
|

Detecting cholangiocarcinoma in patients with primary sclerosing cholangitis – The promise of DNA methylation and molecular biomarkers

Abstract: Cholangiocarcinoma (CCA) is a highly fatal malignancy of the bile ducts that arises in up to 20% of patients with primary sclerosing cholangitis (PSC). Current detection methods for CCA display suboptimal sensitivity and/or specificity, and there is no evidence-based screening strategy for CCA in patients with PSC. Consequently, CCA is often detected too late for surgical resection, contributing to the high mortality associated with this malignancy. Recently, biomarkers have emerged with potential to complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…In order to better characterise and manage CCA, it is commonly classified into three subtypes according to its anatomical location: (1) Intrahepatic (IHCCA), which is located proximally to the second order branches of the left or right hepatic duct; (2) Perihilar (PHCCA) or Klatskin tumour, which is located between the second order branches of the left or right hepatic duct and the CD confluence; and (3) Distal (DCCA), which is located between the CD confluence and the ampulla of Vater[ 4 , 117 ]. PHCCA is the most common type (50%), followed by DCCA (40%) and IHCCA (10%)[ 10 ]. According to its pattern of growth and macroscopic appearance, CCA may present in three different types: Mass-forming (which presents with a mass), periductal-infiltrating (growing along the wall of the bile duct) and intraductal-growing (with intraluminal growth)[ 117 , 118 ].…”
Section: Anatomical Location and Macroscopic Morphology Of Ccamentioning
confidence: 99%
See 3 more Smart Citations
“…In order to better characterise and manage CCA, it is commonly classified into three subtypes according to its anatomical location: (1) Intrahepatic (IHCCA), which is located proximally to the second order branches of the left or right hepatic duct; (2) Perihilar (PHCCA) or Klatskin tumour, which is located between the second order branches of the left or right hepatic duct and the CD confluence; and (3) Distal (DCCA), which is located between the CD confluence and the ampulla of Vater[ 4 , 117 ]. PHCCA is the most common type (50%), followed by DCCA (40%) and IHCCA (10%)[ 10 ]. According to its pattern of growth and macroscopic appearance, CCA may present in three different types: Mass-forming (which presents with a mass), periductal-infiltrating (growing along the wall of the bile duct) and intraductal-growing (with intraluminal growth)[ 117 , 118 ].…”
Section: Anatomical Location and Macroscopic Morphology Of Ccamentioning
confidence: 99%
“…PSC-associated CCA is not diagnosed until intended OLT or at autopsy, in up to 40% of patients[ 10 ]. Surgery is the only potentially curative treatment for all anatomical subtypes of CCA, either in the form or resection or OLT with or without neoadjuvant or adjuvant therapy, which is mainly offered in highly selected patients with early stage PHCCA[ 10 , 11 , 98 , 117 , 148 ].…”
Section: Treatment and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of CA 19-9 in patients with PSC is particularly helpful and can help with the diagnosis of CCA, especially if there is a sudden increase in the level [18] . Studies on CA 19-9 have shown wide variations in sensitivity (46%-90%) and specificity (54%-98%) [19][20][21] . It can be elevated in benign conditions like cholangitis, biliary obstruction due to other reasons, liver cirrhosis and other malignancies like pancreatic cancer.…”
Section: Tumor Markersmentioning
confidence: 99%